Hi!
Given these two equations:
[tex]x = y + 8[/tex]
[tex]x + 4 = 2(y + 4)[/tex]
We want to solve using the substitution method. Knowing that x is equal to y + 8, we can simply plug in 'y + 8' in for x in the second equation, like so:
[tex](y+8)+4=2(y+4)[/tex]
Combine like terms on both sides:
[tex]y+12=2y+8[/tex]
Subtract y from both sides:
[tex]12=y+8[/tex]
Subtract 8 from both sides:
[tex]y=4[/tex]
Now, we can simply plug the y value in to the first equation, and solve for x:
[tex]x=4+8[/tex]
Simplify:
[tex]x=12[/tex]
Therefore, x is equal to 12 and y is equal to 4.
Learn more about the substitution (and also elimination!) method here:
https://brainly.com/question/14619835